Microstructure of intercritical heat affected zone and toughness of microalloyed steel laser welds; Materials Science and Engineering: A; Vol. 770 - Derevyagina L. S. Lyudmila Sergeevna; Gordienko A. I. Antonina Ildarovna; Orishich A. M. Anatoliy; Malikov A. G.; Surikova N. S. Natalya; Volochaev M. N. Mikhail (2020, 2020)
Title screen